Meister Eckhart and the Beguine Mystics : Hadewijch of Brabant, Mechthild of Magdeburg, and Marguerite Porete /: Hadewijch of Brabant, Mechthild of Magdeburg, and Marguerite Porete. (2001 ©1994) - Unknown
No abstract available